1983
DOI: 10.1246/cl.1983.815
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Dioxide as Specific Redox Catalyst in the Photosensitized Oxygen Generation From Water

Abstract: Catalytic formation of oxygen from water was observed in the photosensitized reaction by trisbipyridineruthenium(II) using manganese dioxide as a redox catalyst and pentaammine chlorocobalt(III) as an electron acceptor in acidic solution. The β- and “activated” materials are found to be the most efficient and specific redox catalysts, and a 230% of O2 yield based on MnO2 is obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Taking early studies of electro-or photon-driven Co and Mn oxide catalysts as point of departure [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16], development of nanostructured forms of these oxides featuring very high surface areas have dramatically increased turnover frequencies of O 2 product formation per projected catalyst area [17][18][19]. The need for high turnover frequency per projected area in artificial photosynthesis is based on the requirement that the catalyst should keep up with the incident solar flux in order to minimize wasting of photons.…”
Section: Introductionmentioning
confidence: 99%
“…Taking early studies of electro-or photon-driven Co and Mn oxide catalysts as point of departure [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16], development of nanostructured forms of these oxides featuring very high surface areas have dramatically increased turnover frequencies of O 2 product formation per projected catalyst area [17][18][19]. The need for high turnover frequency per projected area in artificial photosynthesis is based on the requirement that the catalyst should keep up with the incident solar flux in order to minimize wasting of photons.…”
Section: Introductionmentioning
confidence: 99%
“…In ac- [50,89,90] as well as for the active biomimetic CaMn 2 O 4 ·H 2 O mineral phase (see Table S4 for comparison). [43] In fact, our results underline again that biomimicking heterogeneous manganese oxides can be highly efficient even in the absence of calcium or any other alkali and alkaline earth metals.…”
mentioning
confidence: 99%
“…Arange of different types of manganese oxideshave already been tested for WOC, albeit rarely under identical experimental conditions. [6,8,12,13,[17][18][19][20][21][22][23] Instead, catalyst concentrations,o xidising agents, pH regime and so forth differedg reatly from study to study,a nd the reported WOC rates therefore can hardly be compared. To our knowledge, in only one report to date have WOC rates of more than three different types of manganese oxide been screened in the same catalysis set-up, namely,t he report by Robinson et al in 2013 on as et of crystalline MnO x compounds and their WOC performances.…”
Section: Introductionmentioning
confidence: 99%
“…Given this large variety of solid‐state structures and the known WOC activity of some manganese oxides, different factors have been suggested to be important for the catalytic process: 1) similar to the OEC, flexible structures should be beneficial for substrate binding and oxidation‐state changes,5, 9, 10, 12, 18 2) high surface areas result in good accessibility of the catalytically active centres,7, 12, 13, 19, 20, 25 3) average Mn oxidation states greater than +3.5 often provide enough thermodynamic driving force for water oxidation,7, 18, 22, 26 4) secondary cations such as (Lewis acidic) Ca 2+ assist water oxidation by activation of the H 2 O substrate10, 12, 13 and 5) good conductivity of the oxide enhances performance, because WOC requires that four oxidation equivalents accumulate at the (so far unidentified) catalytic sites in the MnO x 9. 18 Some of these factors are obviously contradictory to each other, and so there is currently no real consensus on the most important structural parameters influencing WOC activities of manganese oxides.…”
Section: Introductionmentioning
confidence: 99%